URINARY TRACT INFECTION IN WOMEN (Western European Journal of Medicine and Medical Science, 2024)
Urinary tract infection (cystitis) is one of the most common infectious diseases among women. This condition is observed especially in women of reproductive age and causes inflammatory processes in the lower part of the urinary system. Urinary tract infection not only negatively affects the patient's quality of daily life, but can turn into chronic forms and cause other serious complications. In this article, we will focus on the causes and risk factors, pathogenesis, diagnosis, treatment methods and preventive measures of urinary tract infection in women